Morphology, ultrastructure, and molecular phylogeny of the unarmoured dinoflagellate Kirithra sigma sp. nov. (Ceratoperidiniaceae, Dinophyceae). Issue 5 (2nd September 2020) - Hu, Zhangxi; Li, Zhun; Deng, Yunyan; Iwataki, Mitsunori; Luo, Zhaohe; Wang, Jinxiu; Sun, Yuanyuan; Zhao, Zengxia; Gu, Haifeng; Shin, Hyeon Ho; Tang, Ying Zhong
ABSTRACT: A Gymnodinium -like dinoflagellate, Kirithra sigma sp. nov ., was isolated from Jiaozhou Bay, China, and the southern coast of Korea, and examined by light, scanning, and transmission electron microscopy. Pigment composition and nuclear-encoded partial large subunit ribosomal RNA (LSU rRNA) gene were determined. Cells were oval-shaped (26.4‒36.4 μm long and 17.7‒27.2 μm wide), with a conical epicone and hemispherical hypocone. Its cingulum and sulcus were deep and wide. The cingulum encircled the cell completely, its ends slightly overlapping and displaced one to two cingular widths; the sulcus and sulcal extension formed a sigmoid curve. The anterior sulcal extension contacted the apical structure complex (ASC). The ASC formed a complete circle, consisting of three parallel series of vesicles, and the amphiesmal vesicles within ASC were arranged with one central vesicle (sometimes two) encircled by approximately three rows of polygonal amphiesmal vesicles. Polygonal amphiesmal vesicles of different sizes covered the whole cell surface. The subspherical nucleus was located in the hypocone. Pigment analysis showed that peridinin was the main accessory pigment. The present species is morphologically similar to Kirithra asteri but differs in numbers and rows of amphiesmal vesicles within the ASC, absence of ventral pore, and a sigmoid curve formed by the sulcus and sulcal extension. The partial LSU rRNA gene sequence ( c . 1400 bases) of K. sigma differed by c . 5.3% from that of K. asteri . Molecular phylogeny revealed that K. sigma formed an independent sister clade to K. asteri, indicating they are congeneric but different species.